Neodymium doped yttrium aluminate synthesis and optical properties – A blue light emitting nanophosphor and its use in advanced forensic analysis. (November 2016) - Darshan, G.P.; Premkumar, H.B.; Nagabhushana, H.; Sharma, S.C.; Prasad, B. Daruka; Prashantha, S.C.
Abstract: A series of neodymium ions activated yttrium aluminate nanophosphors of various concentrations were synthesized by solution combustion method using oxalyl dihydrazide as a fuel. The crystal structure, optical energy gap, luminescent properties and Judd-Ofelt analysis were carried out. The use of the phosphor in revealing/enhancing the fingerprints quality was investigated in detail. The powder X-ray diffraction results confirmed the orthorhombic phase for the prepared samples. From diffuse reflectance spectra, estimated energy gap was found to be in range of 5.38–5.80 eV. The photoemission profile of YAlO3 : Nd 3+ exhibit a blue emission upon 364 nm excitation. Further, the prepared materials were used for enhancing the quality of latent fingerprint technique. The present method was facile and robust for visualization of fingerprint with enhanced sensitivity, low glare light and high efficiency on various surfaces. The demonstrated results on facile detection of fingerprints virtually on any surfaces using YAlO3 :Nd 3+ nanophosphors are versatile tool which hold great promise for practical applications on forensic sciences. Graphical abstract: Highlights: YAlO3 :Nd 3+ nanopowders were used for the rapid visualization of latent fingerprint. Average crystallite size is found to be in the range 30–32 nm from both TEM & PXRD. Blue emission nanophosphor powder material with CCT on the Planckian locus. Prepared materials showed better adherence on porous/nonporous and multicolored surfaces.